Comparison between Fluconazole with Oral Protexin Combination and Fluconazole in the Treatment of Vulvovaginal Candidiasis. (17th October 2012) - Nouraei, S.; Amir Ali Akbari, S.; Jorjani, M.; Alavi Majd, H.; Afrakhteh, M.; Ghafoorian, A.; Tafazzoli Harandi, H.
Abstract : Background . According to the limited studies reporting new treatments for vulvovaginal candidiasis, this study was designed to compare the combination of fluconazole and oral protexin with fluconazole in the treatment of vulvovaginal candidiasis. Methods . A double-blind clinical trial was conducted, involving 90 women who were referred to the gynecology clinic. Vulvovaginal candidiasis was diagnosed with itching, cheesy vaginal discharge, and any one of the following: dysuria, pH < 4.5, dyspareunia, vulvar erythema, or vulvar edema and if branched hyphae and Candida buds were visible after addition of KOH 10% in the culture and the result of cultivation in Sabouraud's dextrose agar medium was positive. Patients were randomly classified into two groups Absence of discharge, itching, and negative culture results 5–7 days after completion of treatment indicated treatment success. Data in this study were analyzed using the SPSS version 17.0 software. Results . The combinations, fluconazole-oral protexin and fluconazole-placebo, were equally effective in reduction of complaints and symptoms, but fluconazole-oral protexin combination elicited a better therapeutic response (χ 2 = 0.01, P = 6.7 ). In addition, fluconazole-oral protexin combination treatment demonstrated better recovery time (t = - 2.04, P = 0.04 ). Conclusion . This study demonstrated that complementary treatment with probiotic Lactobacillus increased the efficacy of fluconazole in treatment of vulvovaginal candidiasis. Further research is recommended.